2005
DOI: 10.1007/s10719-005-0734-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of sialyltransferases involved in the biosynthesis of Lewis antigens in human pancreatic tumour cells

Abstract: The sialylated carbohydrate antigens, sialyl-Lewisx and sialyl-Lewisa, are expressed in pancreatic tumour cells and are related to their metastatic potential. While the action of the fucosyltransferases involved in the synthesis of these antigens has already been investigated, no studies have been carried out on the activity and expression of the alpha 2,3-sialyltransferases in pancreatic tumour cells. We describe the sialyltransferase (ST) activity, mRNA expression, and analysis of the cell carbohydrate struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
(49 reference statements)
3
25
0
Order By: Relevance
“…Now, many sialyltransferases or sialidases have been found to be expressed relatively higher or lower in tumors than in normal tissues. [19][20][21][22] Cancer stem cells or cancer stem-like cells that are especially important with resistance to chemotherapy, radiation and neoplasm metastasis are important models for pathologic and therapeutic study of sias in tumors. Since sialyltransferases and sialidases appear to have important functions in normal stem cells as well as in development.…”
Section: Human Sialyltransferases and Sialidase As Cancer Markers Andmentioning
confidence: 99%
“…Now, many sialyltransferases or sialidases have been found to be expressed relatively higher or lower in tumors than in normal tissues. [19][20][21][22] Cancer stem cells or cancer stem-like cells that are especially important with resistance to chemotherapy, radiation and neoplasm metastasis are important models for pathologic and therapeutic study of sias in tumors. Since sialyltransferases and sialidases appear to have important functions in normal stem cells as well as in development.…”
Section: Human Sialyltransferases and Sialidase As Cancer Markers Andmentioning
confidence: 99%
“…Both, sLe a and sLe x are typical tumor associated carbohydrate antigens and have been implicated with tumor progression and enhanced metastasis formation [40] of different neoplasias including colon and colorectal cancer [41][42][43][44][45][46][47], lung cancer [48][49][50][51], gastric cancer [52,53], pancreatic cancer [54,55], prostate cancer [56,57], and breast cancer [58]. Sialyl Lewis a is a prognostic factor in colon and colorectal cancer whereby increased sLe a levels are associated with a poor prognosis of the afflicted patients [41,42,45].…”
Section: Organ-specific Tumor Spreading Directed By Selectinsmentioning
confidence: 99%
“…In several pancreatic cancer cells the presence of terminal sialic acid sugar moiety on carbohydrate chains is higher due to the overexpression of sialyltransferases (Peracaula et al, 2005). We next determined whether the removal of the terminal sialic acid moiety of underglycosylated mucin sufficient to improve cytotoxic action of 5-FU, or is removal of the entire carbohydrate chain required.…”
Section: Effects Of Removing Sialic Acid Residues On 5-fu Cytotoxicitymentioning
confidence: 99%
“…Analysis of normal and tumour-derived mucins revealed that the carbohydrate chains of mucins are shorter and more sialyated in developing tumours compared to normal tissues (Beum et al, 1999;Peracaula et al, 2005). The synthesis of mucin on the surface of normal epithelial cells is under strict regulation, but in tumours there is an overabundance of mucin mainly due to elevated expression of MUC1.…”
mentioning
confidence: 99%